FEATURES OF PEROXIDIZATION OF LIPIDS AND ITS CORRECTION AT THE PATIENTS OF DUODENAL ULCER - T. V. Тregub; I. V. Pogorelaya; E. G. Lobashova; M. S. Protunkevich (Kazimierz Wielki University, 2015)
Тregub Т. V., Pogorelaya I. V., Lobashova E. G., Protunkevich M. S. Особенности перекисного окисления липидов и его коррекция у больных язвенной болезнью двенадцатиперстной кишки = Features of peroxidization of lipids and its correction at the patients of duodenal ulcer. Journal of Education, Health and Sport. 2015;5(5):538-547. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.35659 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%285%29%3A538-547 http://pbn.nauka.gov.pl/works/684421 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 10.04.2015. Revised 15.05.2015. Accepted: 31.05.2015.   УДК 576.3/.7:615.272.4   ОСОБЕННОСТИ ПЕРЕКИСНОГО ОКИСЛЕНИЯ ЛИПИДОВ И ЕГО КОРРЕКЦИЯ У БОЛЬНЫХ ЯЗВЕННОЙ БОЛЕЗНЬЮ ДВЕНАДЦАТИПЕРСТНОЙ КИШКИ   FEATURES OF PEROXIDIZATION OF LIPIDS AND ITS CORRECTION AT THE PATIENTS OF DUODENAL ULCER   Т. В. Трегуб [1], И. В. Погорелая [1], Е. Г. Лобашова [1], М. С. Протункевич [2] Т. V. Тregub [1], I. V. Pogorelaya [1], E. G. Lobashova [1], M. S. Protunkevich [2]   [1] Одесский национальный медицинский университет, г. Одесса, Украина [2] Одесский национальный университет им. И.И. Мечникова, г. Одесса, Украина   [1] Odessa National Medical University, Odessa, Ukraine [2] Odessa National University named I.I. Mechnikov, Odessa, Ukraine   Summary Aim of work. To study influences of mineral concentrate "Vita" on peroxidization of lipids in red corpuscles and plasma of blood for patients by ulcerous  illness of duodenum. Researches passed on the base of different hospitals Odessa during 5. It was inspected 210 patients in age from 18 to 60  that men there was 75,2 %. Conclusions. Thus, application over of mineral concentrate "Vita" brings to the considerable improvement of clinical flow of duodenal ulser, to the improvement of quality of life and peroxidization of lipids reduces for certain, namely - diminishes maintenance of malonic dialdehyde and diene conugates of the nonsaturated fat acids in plasma and red corpuscles of blood for patients of duodenum ulcer on a background normalization of properties. Keywords: duodenal ulcer, peroxidization of lipids, "Vita".   Резюме Цель работы - исследовать влияние минерального концентрата «Вита» на перекисное окисление липидов в эритроцитах и плазме крови у больных язвенной болезнью двенадцатиперстной кишки. Исследования проходили на базе различных больниц г. Одессы в течение 5 лет. Было обследовано 210 больных в возрасте от 18 до 60 лет, из которых мужчин было 75,2 %. Исследовано, что применение минерального концентрата «Вита» приводит к значительному улучшению клинического течения язвенной болезни двенадцатиперстной кишки, улучшению качества жизни и достоверно снижает перекисное окисление липидов, а именно - уменьшает содержание малонового диальдегида и диеновых конъюгат ненасыщенных жирных кислот в плазме и эритроцитах крови у больных язвенной болезнью двенадцатиперстной кишки на фоне нормализации окислительно-восстановительных свойств. Ключевые слова: язвенная болезнь двеннадцатиперстной кишки, перекисное окисление липидов, «Вита».